Prioritization of Economically Important Cattle Diseases Using Participatory Epidemiology Tools in Lalibela, Sekota, and Ziquala Districts of Amhara Region, Northern Ethiopia - Adane Bahiru; Ayalew Assefa (Veterinary Medicine International)
Ethiopia’s livestock resource is one of the largest globally. It is estimated at around 59.5 million cattle, about 30.5 million sheep, and 30.2 million goats. The sector is irreplaceable in the means of livelihood of the population as a source of meat, milk, drought power, and income. Yet, the country is unable to exploit the sector entirely because of highly prevalent infectious diseases and lack of appropriate disease control policy. These constraints are worse in districts of Lalibela, Sekota, and Ziquala, where this specific study was carried out. Despite the availability of scanty animal health services in these areas, information on animal health, especially cattle, was never a significant focus of research. This study was conducted with the objectives of identifying and prioritizing primary cattle disease with the aid of participatory epidemiology tools. Focus group discussions (FGD) and questionnaires were used in prioritizing the top economically important cattle diseases of the selected areas. Accordingly, the result of FGD indicated that ectoparasites, CBPP, FMD, blackleg, bloody diarrhea, and pasteurellosis were the major diseases affecting cattle production in the area. These areas can be representative of most of the countries where a mixed farming system is practiced. Therefore, this result can be used as a basis for broader planning of prevention and control strategies for these kinds of diseases. However, a laboratory-supported extensive investigation of these diseases is highly recommended to validate findings of such types of prioritization of diseases.